'I never wanted my children to see their father the way I've seen mine': caring masculinities and fathering on the Prairies. Issue 1 (2nd January 2021) - Allan, Jonathan A.; Herron, Rachel V.; Ahmadu, Mairo E.; Waddell, Candice; Roger, Kerstin
ABSTRACT: In this article, we draw together literature on rural masculinities, fatherhood, and mental health to explore how men experiencing mental health problems understand fatherhood. Semi-structured qualitative interviews were conducted with 24 men who reside in rural southern Manitoba with a focus on mental health and wellness, perceptions of masculinity, support and living well. In this study, it became apparent that fatherhood was a theme that many of the participants reflected on in response to our questions about their mental health and wellness. It is notable that fatherhood emerged as a key theme related to mental health for those men who had children. This article examines how these men spoke about fatherhood and specifically, how they struggled to negotiate alternative masculinities when working with their fathers, their experiences of aggression, desires to be a better father that their father, and their reflections on changing practices. We argue that fathering can provide a transformative space and hopeful practice for rural men experiencing mental health and emotional distress. In doing so, our paper contributes to research on changing masculinities and the consequences for challenging normative masculinities in rural space.